Teachers’ perception toward character education of early childhood education - Turini Erawati (Jurnal Konseling dan Pendidikan, 2021)
Character education must be started from an early age through formal and nonformal education. The perception of the teacher to a science taught is very important. The aims of research are : (1) analyzing teacher’ perception  towards character education in Early Childhood Education in Sunyaragi Village and (2) factors that influence character education in Early Childhood Education in Sunyaragi. This study used qualitative descriptive. The objects of this research were Play Group Annisa, Persil and Pelangi Sunyaragi. The techniques of data collection are Interview and  observation; (a) Interviews are conducted to early chilhood teachers as many as 12 teachers, and (b) Questioner and (c) Observations are carried out to observe, know all activities organized by all components. To obtain accurate data, the researchers used data analysis techniques presented by Miles and Huberman namely: (a) Data Collection (b) Data Reduction, (c) Data Display , and (d) Conclusion (Drawing and Verifying ) The results of the study are (1) The teacher's perception of character values taught in the education process in Early Childhood Education Playing Group Annisa, Pelangi and Persil Sunyaragi are considered good, and (2) Factors that affect character education in Early Childhood Education are inhibition factors and supporting factors.